Deciphering the number and location of active sites in the monomeric glyoxalase I of Zea mays - Gonzalez, Javier Marcelo (2019)
Detoxification of methylglyoxal, a toxic by-product of central sugar metabolism, is a major issue for all forms of life. The glyoxalase pathway evolved to effectively convert methylglyoxal into d-lactate via a glutathione hemithioacetal intermediate. Recently, we have shown that the monomeric glyoxalase I from maize exhibits a symmetric fold with two cavities, potentially harboring two active sites, in analogy with homodimeric enzyme surrogates. Here we confirm that only one of the two cavities exhibits glyoxalase I activity and show that it adopts a tunnel-shaped structure upon substrate binding. Such conformational change gives rise to independent binding sites for glutathione and methylglyoxal in the same active site, with important implications for the molecular reaction mechanism, which has been a matter of debate for several decades. Database: Structural data are available in The Protein Data Bank database under the accession numbers 6BNN, 6BNX, and 6BNZ.